Theology in the Public Sphere in the Twenty-First Century - Massingale, Bryan N. (2016)
Several decades ago David Tracy wrote that theologians speak to three publics: the academy, the church, and society. Since then many theologians have exhibited, in Tracy's words, "that drive to publicness which constitutes all good theological discourse[,] . a drive from and to those three publics." Our four roundtable authors discuss how and why theologians engage the public sphere in the twenty-first century. In arguing for the necessity of such engagement, they also draw attention to the promise and perils of doing public theology today.
Keywords: Neoliberalism; Nones; blogosphere; Liturgical Theology; Public Theology; Racism; Religious Diversity